Adopsi Nilai-Nilai Islam pada Instrumen Kebijakan Moneter dalam Mengontrol Peredaran Uang - Sri Ayu Andari Putri Alwaris; Nugraha Hasan (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2023)
This study identifies monetary policy instruments that can be adopted or adapted to Islamic values to achieve the goal of controlling the circulation of money. Monetary policy has a central role in managing a country's economy, and the adoption of Islamic values in monetary policy instruments is increasingly gaining attention in the context of Islamic economics. This research uses a library approach by analyzing information sourced from articles, books, journals and various other documentation. The findings of this study explain that the adoption of Islamic values in monetary policy instruments can provide significant benefits in achieving sustainable economic goals and in accordance with Sharia principles. However, implementation challenges are also a concern, including technical aspects and a deep understanding of the principles of Islamic economics. Therefore, we propose practical guidance for monetary authorities in implementing monetary policy instruments inspired by Islamic values. Thus, contribution in formulating alternative monetary policies that integrate Islamic values with modern practices, as well as encourage the development of a more inclusive and sustainable economic system.